Comparison between Flexor Carpi Radialis and Flexor Carpi Ulnaris Tendon Transfer for Fingers’ Extension in High Radial Nerve Palsy - Sen, Sumon Kumar; Datta, Nakul Kumar; Misra, Dipendra; Khan, Zahidul Hak; Islam, Jahidul; Sen, Susmita; Chowdhury, Rumpa Mani; Das, Krishna Priya (Bangladesh Medical Journal, 2021)
The hand grip is severely impaired following high radial nerve palsy due to loss of extension of the wrist, metacarpo- phalangeal joint of fingers and thumb. If radial nerve does not show neural recovery following conservative or surgical repair during the optimum time, tendon transfer is considered the standard treatment. To evaluate and compare the clinical outcome between flexor carpi radialis and flexor carpiulnaris tendon transfer for fingers’ extension in high radial nerve palsy. This randomized controlled trial study was carried out in the Department of Orthopedic Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka over a period of two years from January 2013 to December 2014. A total of 30 patients with high radial nerve palsy were recruited, 15 patients were gone through Flexor Carpi Radialis tendon transfer procedure (FCR group) and the rest 15 patients were gone through Flexor Carpi Ulnaris tendon transfer procedure(FCU group). The patients were followed up for 12 weeks after surgical intervention. Out of all patients, 86.7% male were encountered in each group. The mean age was found 31.07±9.14 years in FCR group and 33.60±10.79 years in FCU group. Humerus fracture was remained a major cause of radial nerve palsy in both FCR and FCU groups (26.7% vs. 33.3%). In final follow-up at 12th week, no extension deficit was observed at MCP joint (93.3% vs. 80.0%, p>0.05).The end result of surgical intervention was found satisfactory equally in both the groups (86.7%). In case of high radial nerve palsy, both FCR and FCU tendon transfer procedures are effective forfingers’ extension at MCP joint. Bangladesh Med J. 2019 Sep; 48 (3): 9-15